Uji Bioaktivitas Ekstrak Daun Sirih Keraton (Cissus discolor) sebagai Antioksidan dan Antibakteri terhadap Escherichia coli - Salim, Apriliani Eka Syakira; Afdhalia, Sinar; Azikra, Nurul; Bau, Andi Besse Tenri; Marzukah, Marzukah (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
This study aims to explore and identify the potential of betel palace leaves (Cissus discolor) as a natural antibiotic candidate in overcoming increasing bacterial resistance. Conventional antibiotic resistance has become a serious problem in the treatment of various diseases caused by pathogenic bacteria such as Escherichia coli. Betel palace leaf is one of the traditional plants believed to have antibacterial and antioxidant properties. However, it has not been widely explored scientifically. The research method used was a mixed method involving exploratory and experimental approaches. Exploration was conducted to identify the morphology and characteristics of the betel palace plant. The research design used a completely randomized design (CRD) with three variations of extract concentration, namely 50%, 75%, and 100%, as well as positive control (chloramphenicol) and negative control (distilled water). Antibacterial test was conducted against E. coli bacteria using the disc diffusion method. Antioxidant test with DPPH method was tested in various concentrations of 10%, 20%, 50%, 100%, 150%. Phytochemical screening test was used to identify bioactive compounds in the extract. The results showed that the keraton betel leaf extract had weak to moderate antibacterial activity with the largest zone of inhibition obtained at 100% extract concentration. This research contributes to the development of herbal medicine by providing new scientific data related to the potential of Cissus discolor as a source of antibacterial compounds and antioxidants.